A new species of Quadrivisio (Amphipoda, Maeridae) from coastal tropical lagoons (Benin, West Africa) - Gnohossou, Pierre; Piscart, Christophe (European Journal of Taxonomy, 2019)
During a recent investigation of the benthic macrofauna from coastal lagoons of southern Benin (Ahémé, Nokoué and Porto-Novo lagoons), a new species of the amphipod genus Quadrivisio Stebbing, 1907, Q. laleyei sp. nov. was collected by means of different quantitative and non-quantitative methods (plastic baskets, wooden artificial substrates, uprooted plants and Surber net) in their intertidal macrophyte zone. The new species can be easily distinguished from most of the other species of the genus by the setation of the mandibular palp and telson and a reduced number of articles (4–6) on the accessory flagellum of the first antenna. The new species closely resembles to Q. lutzi (Shoemaker, 1933) but clearly differ by a reduced armature of the urosomites 1 and 2 and by the geographical distribution (Q. lutzi being known only in Central and South America). Ecological data and an updated key to a species in the genus Quadrivisio are provided.